Neonatal outcomes in obese mothers: a population-based analysis - Minsart Anne-Frederique; Buekens Pierre; De Spiegelaere Myriam; Englert Yvon (BMC, 2013)
Abstract Background If it is well known that obesity increases morbidity for both mother and fetus and is associated with a variety of adverse reproductive outcomes, then few studies have assessed the relation between obesity and neonatal outcomes. This is the aim of the present study after taking into account type of labor and delivery, as well as social, medical and hospital characteristics in a population-based analysis. Methods This study used 2009 data from the Belgian birth register data pertaining to the regions of Brussels and Wallonia and included 38,675 consecutive births. Odds ratio and 95% confidence intervals for admission to neonatal intensive care unit, Apgar score, and perinatal mortality were calculated by logistic regression analyses adjusting for medical, social and hospital characteristics using obesity as the primary independent variable. The impact of analyzing all delivery sites together was tested using mixed-effect analyses. Results The adjusted odds ratio for neonatal intensive care unit admission was higher for obese mothers by 38% compared to non-obese mothers (95% confidence interval (CI): 1.22-1.56), and by 45% (CI: 1.21-1.73) and 34% (CI: 1.10-1.63) after spontaneous and induced labour respectively. The adjusted odds ratio was 1.18 (CI: 0.86-1.63) after caesarean section. The adjusted odds ratio for 1 minute Apgar score inferior to 7 was higher for obese mothers by 31% compared to non-obese mothers (CI: 1.15-1.49) and by 26% (CI: 1.04-1.52) and 38% (CI: 1.12-1.69) after spontaneous and induced labour respectively. The adjusted odds ratio was 1.50 (CI: 0.96-2.36) after caesarean section. The adjusted odds ratio for perinatal mortality was 1.36 (CI: 0.75-2.45) for obese mothers compared to non-obese mothers. Conclusions Neonatal admission to intensive care and low Apgar scores were more likely to occur in infants from obese mothers, both after spontaneous and induced labor.